Association of Autoimmune Thyroiditis and Systemic Lupus Erythematosus - Abd, Wisal Salman (Al-Nahrain Journal of Science, 2012)
This study was designed to investigate the relationship between Systemic Lupus Erythematosus (SLE) and autoimmune thyroiditis disease. Forty one SLE patients diagnosed by latex agglutination test with twenty age and sex matched controls were included in this study. Results revealed that twenty one (51%) of SLE patients had antithyroglobuline antibody and ten of the SLE had elevated TSH. These results suggests that there was an association between SLE and autoimmune thyroiditis.